Analisis Pendapatan dan Faktor yang Mempengaruhi Produksi Susu Sapi Segar di Usaha Susu Sapi Sumber Mulya di Desa Sukasari Kecamatan Kabawetan Kabupaten Kepahiang - Juleha Hapita; Mira Yanuarti; Anadiya Pingki; Dwita Prisdinawati (Pusat Riset dan Inovasi Nasional, 2025)
This study was conducted in February - March 2025 at Sumber Mulya Cow Milk located in Sukasari Village, Kabawetan District, Kepahiang Regency. This study aims to 1). To find out how much income is in the Sumber Mulya cow milk business in Sukasari Village, Kabawetan District, Kepahiang Regency. 2). To find out what factors influence the production of fresh cow's milk in the Sumber Mulya cow milk business in Sukasari Village, Kabawetan District, Kepahiang Regency. The respondents in this study were the owners of the Sumber Mulya Cow Milk Business in Sukasari Village, Kabawetan District, Kepahiang Regency. The method of determining respondents was carried out by purposive sampling with the consideration that the business owner was successful in cultivating dairy cattle and producing fresh cow's milk. The data analysis method used in this study was revenue analysis, income analysis and cobb-dauglass function analysis and using multiple linear regression. The results of the study that the regression equation shows a constant value of α of -8.068 if the Labor Variable (X1), Amount of Feed (X2), Amount of Water (X3) then the Production Variable (Y) is -8.068. The influence of the labor variable (X1), Amount of feed (X2) and amount of water (X3) on cow's milk production (Y), then the significance value is obtained .000 < 0.05 or 5% then it can be concluded that the independent variables have a significant effect simultaneously (together) on the dependent variable, with a calculated f value of 13.995 > f table 3.35 which shows the calculated f value is greater than the f table and there is a significant influence on the three independent varimuables on the dependent variable.